Three-dimensional kinetics of the shoulder, elbow, and wrist during a penalty throw in water polo - Feltner, M. E.; Taylor, G. (Journal of Applied Biomechanics, 1997)
The purpose of the study was to examine the resultant joint forces (RJFs) and torques (RJTs) at the shoulder, elbow, and wrist during penalty throws and determine the relationships between muscle actions and motions of the throwing arm. Subjects with an overhand (OH) throwing technique created larger maximal and average RJTs at the shoulder and elbow compared to subjects with a sweep (SW) technique (Feltner & Nelson, 1996). Prior to release, OH technique subjects decreased their abduction torque and created adduction torques at the shoulder. Adduction torques and downward vertical motion of the trunk, together with an internal rotation torque at the shoulder, resulted in large internal rotation angular velocities at release for the OH technique subjects. The SW technique subjects did not exhibit these technique characteristics. Additionally, throwing technique exhibited a moderate but positive relationship with several chest, upper arm, and forearm circumference measures. Findings suggest that muscular strength may be a causal determinant of technique style.